Translating Quoted Sacred Texts in Political Speeches - Soliman, Hussam El Din Mohamed (2006)
A Master of Arts Thesis in English Arabic English Translation and Interpreting Submitted to the College of Arts and Sciences by Hussam El Din Mohamed Soliman Entitled, "Translating Quoted Sacred Texts in Political Speeches," December 2006. Available are both Soft and Hard Copies of the Thesis.